Kinetic Analysis for Macrocyclizations Involving Anionic Template at the Transition State - Vicente Martí-Centelles; M. Isabel Burguete; Santiago V. Luis (The Scientific World Journal)
Several kinetic models for the macrocyclization of a C2 pseudopeptide with a dihalide through a SN2 reaction have been developed. These models not only focus on the kinetic analysis of the main macrocyclization reaction, but also consider the competitive oligomerization/polymerization processes yielding undesired oligomeric/polymeric byproducts. The effect of anions has also been included in the kinetic models, as they can act as catalytic templates in the transition state reducing and stabilizing the transition state. The corresponding differential equation systems for each kinetic model can be solved numerically. Through a comprehensive analysis of these results, it is possible to obtain a better understanding of the different parameters that are involved in the macrocyclization reaction mechanism and to develop strategies for the optimization of the desired processes.